The future of the professions how technology will transform the work of human experts - Susskind, Richard E.; Susskind, Daniel (Oxford University Press, 2015)
This book predicts the decline of today's professions and describes the people and systems that will replace them. In an Internet society, according to Richard Susskind and Daniel Susskind, we will neither need nor want doctors, teachers, accountants, architects, the clergy, consultants, lawyers, and many others, to work as they did in the 20th century.